1997
DOI: 10.1021/cm9603718
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and Electronic Structures of New π-Conjugated Pyrrole− and Furan−Nonheterocycle Copolymers

Abstract: The geometrical and electronic structures of new hypothetical pyrrole-and furannonheterocycle copolymers were theoretically investigated. Nonheterocycles include cyclopentadiene, silole, oxocyclopentadiene, and thiocyclopentadiene, whose homopolymers are of the quinoid forms in their ground states. AM1 band calculations show that in the ground states the aromatic forms of the copolymers containing cyclopentadiene or silole rings are more stable than the quinoid types, whereas the aromatic forms of the oxocyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Tamao et al have previously reported similar results of MO calculations for some heterocycles, including silole, pyrrole, furan, and thiophene; of these silole has the smallest HOMO−LUMO gap, arising primarily from its lower-lying LUMO 2a…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Tamao et al have previously reported similar results of MO calculations for some heterocycles, including silole, pyrrole, furan, and thiophene; of these silole has the smallest HOMO−LUMO gap, arising primarily from its lower-lying LUMO 2a…”
Section: Resultsmentioning
confidence: 60%
“…π-Conjugated systems containing silole rings are of current interest because of their unique optical and electrical properties. Both experimental and theoretical studies have demonstrated that the silole ring system possesses a particularly low-lying LUMO, presumably due to the orbital interaction between the σ* orbital of the silole silicon atom and the π*-orbital of the butadiene fragment, namely σ*−π* conjugation …”
Section: Introductionmentioning
confidence: 99%
“…The remarkably red-shifted UV absorptions and high electron-transporting properties of the compounds containing the silole ring would result from their low-lying lowest unoccupied molecular orbital (LUMO) due to the σ*−π* interaction between the silole silicon atom and the π-orbitals . Although many papers concerning the synthesis of polymers and oligomers containing the silole ring have been published to date, , only a few refer to polymers bearing 2,5-linked silole rings in the backbone . In the course of studies concerning the synthesis of silole-containing conjugated polymers, , we have prepared polymers having repeating organosilicon-2,5-diethynylenesilole units in the backbone, by dehydrobromination of 2,5-dibromosilole and diethynyldi- and monosilanes in the presence of a CuI/Pd(PPh 3 ) 4 catalyst…”
mentioning
confidence: 99%
“…Results and Discussion. The starting monomer 2,5-dibromo-1,1,3,4-tetraphenylsilole ( 1 ) was prepared as reported by Tamao et al6b Tamao et al have also reported the synthesis of 2,5-bis(phenylethynyl)-1,1,3,4-tetraphenylsilole from the reaction of 1 and phenylacetylene in the presence of a CuI/Pd(PPh 3 ) 4 catalyst in a mixed solvent of THF and triethylamine 6b. First, we examined a model reaction to confirm that CuI/Pd(PPh 3 ) 4 -catalyzed dehydrobromination is applicable to the synthesis of 2,5-bis(silylethynyl)silole.…”
mentioning
confidence: 99%
“…Current interest has been focused on the chemistry of the silole ring system, which shows unique optical properties. The characteristic red-shifted UV absorptions of silole derivatives originate from their low-lying LUMO that is due to the σ*−π* interaction between the silole silicon atom and the π-orbitals . Highly electron transporting properties of cooligomers of silole-2,5-diyl and heteroaromatic systems and dithienosiloles having a silole ring fused with two thiophene rings also reflect the low-lying LUMO of the silole ring systems.…”
Section: Introductionmentioning
confidence: 99%